Surgical Management of Gestational Gigantomastia: A Case Report Highlighting Therapeutic Intervention - Misha A. Lemma, MD; Yisihak S. Debodina, MD; Martha F. Gebremedhin, MD; Meki K. Aman, MD; Don Eliseo III Lucero-Prisno, MD, MSc, PhD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Gigantomastia is an exceedingly rare condition characterized by extraordinary growth of breasts during pregnancy, and its underlying etiology remains elusive. Although surgical intervention is the primary treatment modality, there have been emerging prospects for utilizing adjunctive medical therapies, such as bromocriptine, to address this challenging condition. Herein, we report the case of a 26-year-old woman who experienced abrupt and asymmetric bilateral breast enlargement commencing in the second month of her pregnancy. Remarkably, this enlargement persisted for an extended duration of 3 years. Despite the absence of prior medical therapy involving bromocriptine or other interventions, the patient ultimately underwent a simple mastectomy coupled with nipple-areola complex reconstruction. Although bromocriptine treatment holds potential benefits, its availability may vary in different healthcare settings. Therefore, the consideration of surgical management as an alternative approach becomes crucial, particularly when bromocriptine is not accessible or proves ineffective. This approach ensures the appropriate management of gestational gigantomastia, with the choice of treatment tailored to the individual patient’s needs and resource availability.